Juridical Review of the Criminal act of Cigarette Circulation Without Excise Tape According to Law Number 39 of 2007 Concerning Excise - Sinton Salfator Manullang; Kusno Kusno; Toni Toni (International Journal Labs, 2022)
Background: In Article 1 paragraph (3) of the 1945 Constitution, it is stated that the State of the Republic of Indonesia is a country of law where the law is used as the commander-in-chief to realize truth and justice in Indonesia. Law is a series of rules that master certain behaviors and deeds of human life in social life. Objective: This study aims to find out and analyze the legal regulation of the circulation of cigarettes without excise in Indonesia. As well as knowing and analyzing law enforcement against the circulation of non-excise cigarettes in Indonesia. Methods: This research belongs to the normative type of research. So that it can be known that legal cigarette distribution in Indonesia can be measured through business legality, product legality, and the legality of advertising and promotion as a means of circulation. Result: Regarding the legal regulation on the circulation of non-excise cigarettes in Indonesia, namely because cigarettes are included in the characteristics of excisable goods regulated in Law Number 39 of 2007. Furthermore, law enforcement against the circulation of cigarettes without excise can be subject to criminal penalties in the form of imprisonment and fines which are cumulative (combined) criminal penalties. Conclusion: Based on the explanation above, it can be concluded that cigarettes that are legally distributed in Indonesia can be measured through business legality, product legality, and the legality of advertising and promotion as a means of circulation.